Dual nature of magnetic dopants and competing trends in topological insulators - Paolo Sessi (Nature Portfolio, 2016)
Magnetic impurities break time reversal symmetry in topological insulators, but there has been disagreement between theory and experiment. Here, the authors study the response of topological states to magnetic dopants at the atomic level and show that, contrary to what generally believed, magnetic order and gapless states can coexist.